UTILIZATION OF TELEHEALTH ON THE PATIENTS WITH POSTTRAUMATIC STRESS DISORDER (PTSD) [PENGGUNAAN TELEHEALTH PADA KLIEN DENGAN POSTTRAUMATIC STRESS DISORDER (PTSD)] - Shinta Yuliana Hasibuan; Rr. Tutik Sri Hariyati (Universitas Pelita Harapan, 2020)
The development of the industrial revolution 4.0 revolution affected various aspects of life also the environment. This is seen by the technological advances in the health sector, namely telehealth. Telehealth is one of the solutions in providing nursing care, one of which is patients with posttraumatic stress disorder (PTSD). Telehealth for patients with PTSD enables patients to be able to get treatment wherever and whenever the patient wants. The presence of telehealth will enable patients to reduce the symptoms of PTSD. Telehealth service systems use the internet with videoconferencing, eMental, telehealth video systems at home. With telehealth this also helps to erase the distance between communities, disabilities and elderly people living in rural areas, so they can get the right treatment. The writing of this scientific paper is expected to be able to describe the use of telehealth in patients with PTSD. This research method uses a literature review that focuses on the use of telehealth. The application of telehealth will have an impact on reducing the symptoms of PTSD. The results of this review literature found two of the five articles found containing a comparison between direct treatment and treatment via telehealth. Two studies on the application of telehealth at home and one article on the effectiveness of telehealth use in patients with PTSD.BAHASA INDONESIA Perkembangan revolusi industri 4.0 memengaruhi berbagai aspek kehidupan dan juga lingkungan sekitar. Hal ini dilihat dengan adanya kemajuan teknologi dalam bidang kesehatan yaitu telehealth. Telehealth merupakan solusi dalam memberikan asuhan keperawatan, salah satunya pasien dengan posttraumatic stress disorder (PTSD). Telehealth bagi pasien dengan PTSD memampukan pasien untuk dapat mendapatkan treatment dimanapun dan kapanpun pasien mau. Adanya telehealth akan memampukan pasien untuk menurunkan gejala dari PTSD. Sistem layanan telehealth menggunakan internet dengan system video conference, eMental, video telehealth di rumah. Dengan adanya telehealth hal ini juga membantu menghapuskan jarak antara masyarakat, disabilitas dan usia lanjut yang hidup di pedesaan sehingga mereka mampu mendapatkan treatment yang tepat. Penulisan karya ilmiah ini diharapkan dapat mendeskripsikan penggunaan telehealth pada pasien dengan PTSD. Metode penelitian ini menggunakan literature review yang berfokus pada penggunaan telehealth. Penerapan telehealth akan berdampak pada berkurangnya gejala-gejala dari PTSD. Hasil literature review ini menemukan dua artikel dari lima yang didapatkan berisi tentang perbandingan antara pemberian terapi secara langsung dan treatment melalui telehealth. Dua studi tentang penerapan telehealth di rumah dan satu artikel tentang keefektifan penggunaan telehealth pada pasien dengan PTSD.